Peer-feedback as a part of collaborative problem solving - Hošpesová, Alena; Novotná, Jarmila; Chan, Esther; Clarke, David (Scientia in educatione, 2022)
The article presents a study within the international project named The Social Unit of Learning. This study examines the ways in which students interact with each other when solving an open mathematical problem in small groups (four students a group). Attention is focused on peer feedback, especially on its form and how it affects the process of solving the problem. From our analysis, feedback appears often in the group discussion and takes the form of both positive (confirmation; question asking for clarification, request for clarification, eliciting) and negative reactions (rejection, explained or unexplained objection, doubt, question involving doubt). The analysis also identified a communication pattern that generalizes the course of the group discussion and factors influencing the quality of peer feedback related to the content structure of the problem (thematic, conceptual and competence layer).